2013
DOI: 10.1515/cclm-2012-0795
|View full text |Cite
|
Sign up to set email alerts
|

Opinion paper on innovative approach of biomarkers for infectious diseases and sepsis management in the emergency department

Abstract: Sepsis is a leading healthcare problem, accounting for the vast majority of fatal events in critically ill patients. Beyond early diagnosis and appropriate treatment, this condition requires a multifaceted approach for monitoring the severity, the potential organ failure as well as the risk of death. Monitoring of the efficacy of treatment is also a major issue in the emergency department (ED). The assessment of critically ill conditions and the prognosis of patients with sepsis is currently based on some scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 37 publications
3
48
0
Order By: Relevance
“…Results from the BACH study also showed that patients with elevated CTproAVP and the lowest levels of sodium had the highest mortality at 90 days. Combined end points of mortality, readmissions and emergency department visits were also associated with higher CTproAVP [37,40].…”
Section: Heart Failurementioning
confidence: 91%
“…Results from the BACH study also showed that patients with elevated CTproAVP and the lowest levels of sodium had the highest mortality at 90 days. Combined end points of mortality, readmissions and emergency department visits were also associated with higher CTproAVP [37,40].…”
Section: Heart Failurementioning
confidence: 91%
“…Recent studies have demonstrated that pregnant women with HG have higher inflammatory markers when compared to healthy pregnant women without HG in the first trimester. Measuring white blood cell count (WBC), neutrophil-to-lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and red blood cell distribution width (RDW) is an inexpensive and convenient way to identify systemic inflammation in the body (12)(13)(14)(15). Studies have shown that NLR, PLR, and RDW values are highly associated with the prognosis of diseases related to inflammation (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Clinical Chemistry and Laboratory Medicine , Di Somma et al [ 12 ] provide an overview about the potential clinical usefulness of some biomarkers of sepsis. This opinion article represents a synopsis of the lectures on biomarkers and sepsis of the Third Italian GREAT Network Congress, which was held in Rome, 15 -19 October 2012.…”
mentioning
confidence: 99%
“…In ref. [ 12 ], the authors discuss not only the biomarkers already standardized and actually used in clinical practice but also some biomarkers that are still tested for experimental use.…”
mentioning
confidence: 99%
See 1 more Smart Citation